ANALISIS DIMENSI INTERKULTURAL ANTAR MASYARAKAT BERAGAMA STUDI FENOMENOLOGI PADA MASYARAKAT KOTA MATARAM - Imam Malik; Syafruddin Syafruddin; Ananda Wahidah; Rismaade Aryat; Izhar Husadi; Muhammad Furqon; Paenal Juni Harian (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
This research aims to measure and analyze intercultural dimensions in the context of creating effective relationships among religious communities and to formulate effective strategies and approaches to mitigate potential conflicts and create harmonious relationships amidst a society with diverse cultures and religions. This research was conducted in the city of Mataram. This research uses a qualitative approach with a phenomenological method to collect data from various religious and cultural groups in different areas of Mataram. The research instruments include in-depth interviews and non-participatory observations; this step was chosen because issues of ethnicity, religion, race, and inter-group relations (SARA) are sensitive topics to discuss. The data collected was then analyzed using a qualitative approach such as content analysis to identify patterns of relationships between religious and cultural groups. The research results show several factors influencing interactions between religious communities, namely the level of education, knowledge about the cultures and religions of each group, and intensive communication. Additionally, it was found that an effective form of interaction is one filled with open dialogue between groups and individual openness to differences in each intercultural interaction session. The findings of this research can serve as a basis for developing policies that support cultural and religious diversity in society and promote understanding and cooperation among religious groups to achieve more harmonious relationships.